Developing a system of temperate and tropical aerobic rice in Asia (STAR) - Bouman, B.A.M. (CGIAR Challenge Program on Water and Food, 2008)
The project “Developing a System of Temperate and Tropical Aerobic Rice in Asia (STAR) undertook strategic research to develop sustainable aerobic rice systems for water- scarce irrigated and rainfed environments in Asia. Aerobic rice is a production system in which specially developed rice varieties are grown in nonsaturated soils without ponded water just like wheat or maize. The target environments are areas where water is too short to grow conventional lowland rice, either rainfed or supplementary irrigated. In the Yellow River Basin of China, with a temperate climate, we have demonstrated that aerobic rice yields of 6 t ha-1 are attainable with about half of the water needed to grow lowland rice. In average rainfall years, farmers would need to give only 2-3 supplemental irrigations. The profitability is comparable with that of other food crops such as maize and soybean, depending on (yearly fluctuating) relative commodity prices (sometime profitability is lower, sometimes higher). Farmers like aerobic rice because it contributes to food self-sufficiency and requires less labor than transplanted lowland rice. It also allows them to diversify their cropping system. Moreover, aerobic rice can stand flooding and is an ideal crop for the large areas that get annually flooded by heavy rainfall or overflowing rivers that destroy the other crops. In the tropics, the development of aerobic rice is less advanced. In central India, in the Indo-Gangetic Plain, we identified rice varieties that can be grown in aerobic conditions, producing 4- 4.5 t ha-1 and using 30-40% less water than lowland rice at the same yield level. In the Philippines, although yield potentials of 6 t ha-1 have been demonstrated, attainable yield ranged from 2.9 to 3.8 t ha-1 in the dry season, and from 3.9 to 4.5 t ha-1 in the wet season. A risk of yield decline was demonstrated at a few sites caused by soil-borne pests (such as nematodes), nutrient disorders, or a combination of both. In our sites in Northeast Thailand and Laos, breeding lines were identified with yield potentials of 2 (Thailand) to 3.5 (Laos) t ha-1. Further research and development is needed to bring tropical aerobic rice to fruition, mainly on variety improvement (increasing yield potential and adaptation to aerobic soil) and sustainability. In conclusion, aerobic rice holds promise for those farmers in water-short irrigated or rainfed environments where water availability at the farm level is too low, or where water is too expensive, to grow flooded lowland rice.